SKRENING BAKTERI TOLERAN PESTISIDA DENGAN BAHAN AKTIF KLORANTRANILIPROL ASAL TANAH PERTANIAN BATURITI TABANAN BALI - WIWIK SINTA DEWI, NI KADEK; DARMAYASA, IDA BAGUS GEDE; SUNDRA, I KETUT (Jurnal Biologi Udayana, 2017)
In Indonesia agriculture practice often used the large scale pesticide application such as insecticide, herbicide, and fungicide. The wide use of toxic pesticide has created numerous problem in increasing environtmental hazard to human and to other animals. Many of soil bacteria had important role to degrading chemical compounds into simpler compounds as a bioremediation agent. The aim of this study was to screen the Chlorantraniliprole tolerant bacteria using soil mineral medium with Prevathon pesticide addition, also teo identificate the species of bacteria. This research was conducted at Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Udayana University. The research was done in three analysis, (1) bacteria test on Prevathon pesticide addition to mineral medium treatment, (2) characterization of bacteria, (3) Identification of pesticide tolerant bacteria with BD BBL Crystal Enteric/Non FermenterID Kit. The results showed that mineral medium with the addition of pesticides Prevathon treatment able to provide a significant different effect on the enrichment stage 1, stage 2 and stage 3 (P<0.05), there was 5 isolates pesticide tolerant bacteria that isolated from Baturiti Tabanan cultivated soil that was BSP 1, BSP 2, BSP 3 known as gram negative bacteria, and BSP 4, BSP 5 known as Gram positive bacteria, pesticide tolerant bacteria identified as Serratia marcescens which is a Gram negative bacteria group and may cause pathogenic.